Answers

2014-10-25T20:04:11+05:30
Tn = (2n-1)2
t₁ = 2
t₂ = 6
t₃=10
the series is in a.p.
d=4
a=2
sum of n terms of ap =n/2 [ 2a+(n-1)d ]
                              =n/2  [ 4+ 4n-4 ]
                              =n/2 [ 4n ]
                              =4n²/2
                              =2n²
0
2014-10-25T20:57:46+05:30
Tn = (2n-1)2
t₁ = 2
t₂ = 6
t₃=10
the series is in a.p.
d=4
a=2
sum of n terms of ap =n/2 [ 2a+(n-1)d ]
                              =n/2  [ 4+ 4n-4 ]
                              =n/2 [ 4n ]
                              =4n²/2
                              =2n² 
                              =2n*2n
                              =4n
0